2009
DOI: 10.1007/s00467-007-0667-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent lymphomatoid papulosis associated with nephrotic syndrome. An occurrence of uncertain origin

Abstract: We report on a 10-year-old child with nephrotic syndrome who developed recurrent lymphomatoid papulosis (LYP) 60 months after the first episode of proteinuria. LYP appeared when the child was taking low-dose cyclosporin and disappeared after the drug was replaced by prednisone at doses utilized for nephrotic syndrome (2 mg/kg). During the tapering of steroids, when the child was treated with low-dose prednisone (0.2 mg/kg), both LYP and nephrotic syndrome started again and required the reintroduction of predni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies of childhood LyP reported a younger mean age of onset (%9 years), a similar presentation with cyclic papulonodular eruptions, and variable response to treatment. 2,4,5,[7][8][9][10][11] The histopathologic features showed a predominance of type A LyP with a polymorphous infiltrate, with or without eosinophils and large atypical CD30 1 lymphocytes, similar to features in adults. 5,6 Previous reports of TCRGR studies showed positive results in two cases without association with lymphoproliferative disorders.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies of childhood LyP reported a younger mean age of onset (%9 years), a similar presentation with cyclic papulonodular eruptions, and variable response to treatment. 2,4,5,[7][8][9][10][11] The histopathologic features showed a predominance of type A LyP with a polymorphous infiltrate, with or without eosinophils and large atypical CD30 1 lymphocytes, similar to features in adults. 5,6 Previous reports of TCRGR studies showed positive results in two cases without association with lymphoproliferative disorders.…”
Section: Discussionmentioning
confidence: 73%
“…Only a few previous reports have detailed the clinical and laboratory features of LyP in pediatric patients. [4][5][6][7][8][9][10] The most common histopathologic subtype described for adult-onset and pediatric-onset LyP is type A, which is characterized by large, atypical, CD30 1 lymphocytes, resembling Reed-Sternberg cells of Hodgkin lymphoma, present in a wedge-shaped distribution throughout the dermis and admixed with various numbers of inflammatory cells. Fewer cases are classified as type B, which is characterized by small, CD30 e lymphocytic cells with cerebriform nuclei in a bandlike pattern, along with epidermotropism.…”
Section: And Although It Is Not Anmentioning
confidence: 99%
“…29 A small number of case reports have suggested that MCNS may be associated with several subtypes of NHL; however, this association has not been studied in depth. 7 , 10 , 13 , 17 , 20 , 21 , 31 These case reports highlight a close relationship between the progression of NHL and MCNS, suggesting that MCNS may be considered as a paraneoplastic glomerulonephritis in the context of NHL. 8 , 19 , 22 , 28 …”
Section: Introductionmentioning
confidence: 71%